INFLUENCE ENVIRONNEMENTALE DE LA VILLE DE KINSHASA SUR LE COMPORTEMENT DES PARENTS DE LA COMMUNE DE NGALIEMA VIS-A-VIS DE LEURS JEUNES FILLES - SINGA, Nathan IUNGBI; FIASOLUA, Wafi WANSENDE; KOBESE, David MWILU; BUJIKA, Marie-Chantal KADIOMBO (Journal of Advance Research in Social Science and Humanities (ISSN 2208-2387), 2024)
This research relates to "environmental influence of the city of Kinshasa on the behavior of the parents of the commune of Ngaliema vis-à-vis their young girls" after having asked a good number of questions to a sample of at least 40 Parents of young girls in the town in the city of Kinshasa in relation to the environmental influence of the city of Kinshasa on their behavior towards their young daughters, the results found demonstrate that clearly that the city environment de Kinshasa has a very negative influence on making parents' decisions towards their young girls, which leads to the depravity of mores in a large number of young girls in the commune Ngaliema in the city of Kinshasa, whose details are in the development of this article.